Pengenalan Bangun Datar dalam Mengembangkan Aspek Kognitif Melalui Permainan Papan Geometri Pintar (Papingeo) pada Anak Usia Dini 5-6 Tahun di TK Pratama Widya Pasraman Gurukula : Introduction of Flat Shapes in Developing Cognitive Aspects Through Smart Geometry Board Games (Papingeo) in Early Childhood 5-6 Years in Widya Pasraman Gurukula Primary Kindergarten - Anggreni Putri Komang Sri; I Made Gede Anadhi (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
Papingeo is a game that uses a geometric board used as an educational game tool that stimulates the development of cognitive aspects of early childhood. Widya Pasraman Gurukula Primary Kindergarten utilizes this game as a cognitive aspect learning process. The purpose of the research is to explore the extent to which this game is useful and effective for early childhood in Widya Pasraman Gurukula Primary Kindergarten. The method used is qualitative with a descriptive approach. Sources of data are teachers and 43 students aged 5-6 years Widya Pasraman Gurukula Primary Kindergarten. Data collection techniques through observation, interviews and documentary studies. Data analysis was carried out using Jean Piaget's cognitive theory and Lev Vygotsky's constructivist learning theory. The results showed that the introduction of flat shapes through the Papingeo game was effective in developing children's cognitive aspects. Through this game, children can become familiar with geometric shapes, strengthen their understanding of size and shape, and develop problem-solving skills, logical thinking, and creativity. In addition, this game also involves social interaction, improves concentration, and creates a fun learning experience. The conclusion of this study is that the Papingeo game can be used as an effective approach in the introduction of flat shapes in children aged 5-6 years, with the potential to improve overall cognitive development. ABSTRAK Papingeo adalah permaianan yang menggunakan papan geometri digunakan sebagai alat permainan edukasi yang menstimulasi perkembangan aspek kognitif anak usia dini. TK Pratama Widya Pasraman Gurukula memanfaatkan permainan ini sebagai salah satu proses pembelajaran aspek kognitif. Tujuan penelitiaan adalah untuk menggali sejauh mana permainan ini bermanfaat dan efektif bagi anak usia dini di TK Pratama Widya Pasraman Gurukula. Metode yang digunakan adalah kualitatif dengan pendekatan deskriptif. Sumber data adalah guru dan 43 siswa usia 5-6 tahun TK Pratama Widya Pasraman Gurukula. Teknik pengumpulan data melalui observasi, wawancara dan studi dokumantasi. Analisis  data dilakukan dengan teori kognitif Jean Piaget dan teori pembelajaran konstruktivis Lev Vygotsky  Hasil penelitian menunjukkan bahwa pengenalan bangun datar melalui permainan Papingeo efektif dalam mengembangkan aspek kognitif anak-anak. Melalui permainan ini, anak-anak dapat mengenal berbagai bentuk geometris, memperkuat pemahaman mereka tentang ukuran dan bentuk, serta mengembangkan keterampilan pemecahan masalah, pemikiran logis, dan kreativitas. Selain itu, permainan ini juga melibatkan interaksi sosial, meningkatkan konsentrasi, dan menciptakan pengalaman belajar yang menyenangkan.  Kesimpulan penelitian ini adalah  permainan Papingeo dapat digunakan sebagai pendekatan yang efektif dalam pengenalan bangun datar pada anak usia 5-6 tahun, dengan potensi untuk meningkatkan perkembangan kognitif  secara menyeluruh.